2022
DOI: 10.3389/fonc.2022.843598
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNA-Derived Small RNAs: Novel Regulators and Biomarkers of Cancers

Abstract: Transfer RNA-derived small RNAs (tsRNAs) are conventional non-coding RNAs (ncRNAs) with a length between18 and 40 nucleotides (nt) playing a crucial role in treating various human diseases including tumours. Nowadays, with the use of high-throughput sequencing technologies, it has been proven that certain tsRNAs are dysregulated in multiple tumour tissues as well as in the blood serum of cancer patients. Meanwhile, data retrieved from the literature show that tsRNAs are correlated with the regulation of the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 152 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…tRF-5s are produced by Dicer cutting the D loop of tRNA; they can be further divided into tRF-5a (14 nt-16 nt), tRF-5b (22 nt-24 nt) and tRF-5c (28 nt-30 nt) ( 4 , 14 ). i-tRFs are derived from the anticodon loop of mature tRNAs and sections of the D-loop and T-loop ( 3 , 14 , 15 ).…”
Section: Biogenesis and Discovery Of Tsrnasmentioning
confidence: 99%
See 3 more Smart Citations
“…tRF-5s are produced by Dicer cutting the D loop of tRNA; they can be further divided into tRF-5a (14 nt-16 nt), tRF-5b (22 nt-24 nt) and tRF-5c (28 nt-30 nt) ( 4 , 14 ). i-tRFs are derived from the anticodon loop of mature tRNAs and sections of the D-loop and T-loop ( 3 , 14 , 15 ).…”
Section: Biogenesis and Discovery Of Tsrnasmentioning
confidence: 99%
“…Studies have shown that tsRNAs have a wide range of biological functions, including regulating the stability of mRNA, translation regulation, and epigenetic regulation (2)(3)(4)15). The biological functions of tsRNAs are very complex and require further elucidation.…”
Section: Biological Functions Of Tsrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on where they cleave from tRNAs, tRFs are divided into four types: tRF-1, tRF-2, tRF-3, and tRF-5. A, B or C subtypes of tRF-5 and tRF-3 can be further categorized ( Yu et al, 2020 ; Fu & Xu, 2022 ). Recent studies have shown that some tRFs may be involved in altering the metabolic pathways underlying breast cancer progression ( Zhu et al, 2021 ; Liu et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%